Brazil’s Africa policy: change between Lula and Dilma? - Ziebell de Oliveira, Guilherme (2015)
Brazilian foreign policy towards Africa has suffered a major inflection from 2003. After a long period of estrangement, the rise to power of Luiz Inácio (Lula) da Silva underscored a clear reorientation of Brazilian foreign policy, and a resumption of the assignment of importance to the African continent. Over the two terms of Lula, Brazil has reconnected Africa, increasing its participation in the continent and making it an important partner, not only politically, but also economically. In 2011, Rousseff became president of Brazil, and Celso Amorim, then foreign minister, was replaced by Antonio Patriota, raising many questions about the directions that would be adopted in the new government's conduct of foreign policy. This paper seeks to analyze whether there has or has not been a shift in Brazil's foreign policy towards Africa in the Rousseff administration in relation to the Lula da Silva government and, if so, how deep has it been. To do so, it relies on the work of Charles Hermann (1990), to analyze the different levels of change in foreign policy; Ricardo Sennes (2003), to demonstrate that there is a continuity in the foreign policy matrix between Lula and Dilma; and Robert Putnam (2010), to demonstrate that the changes that have ocurred are, to a large extent, a reflection of the transformations that have taken place in both the international scenario and the domestic arena.